2013
DOI: 10.1073/pnas.1221652110
|View full text |Cite
|
Sign up to set email alerts
|

Stat2 loss leads to cytokine-independent, cell-mediated lethality in LPS-induced sepsis

Abstract: Deregulated Toll-like receptor (TLR)-triggered inflammatory responses that depend on NF-κB are detrimental to the host via excessive production of proinflammatory cytokines, including TNF-α. Stat2 is a critical component of type I IFN signaling, but it is not thought to participate in TLR signaling. Our study shows that LPSinduced lethality in Stat2 −/− mice is accelerated as a result of increased cellular transmigration. Blocking intercellular adhesion molecule-1 prevents cellular egress and confers survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
4
35
1
Order By: Relevance
“…Compared with WT mice, however, we demonstrated that Park7 −/− mice are more susceptible to LPS-induced sepsis accompanied by impaired cytokine and chemokine production. Interestingly, similar phenomenon was also observed by Foster's group in Stat2 −/− mice [41]. These findings strongly suggest the existence of an alternative, cytokine storm-independent mechanism of LPS-induced septic death.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with WT mice, however, we demonstrated that Park7 −/− mice are more susceptible to LPS-induced sepsis accompanied by impaired cytokine and chemokine production. Interestingly, similar phenomenon was also observed by Foster's group in Stat2 −/− mice [41]. These findings strongly suggest the existence of an alternative, cytokine storm-independent mechanism of LPS-induced septic death.…”
Section: Discussionsupporting
confidence: 87%
“…An MPO assay was performed in the peritoneal fluid as described elsewhere (2,5,11,12). Briefly, 200 μl of peritoneal fluid was incubated with 800 μl hexadecyltrimethylammoniumbromide (HTAB) buffer and the mixture was transferred into microcentrifuge tube and centrifuged at 20,000 ×  g  for 4 min.…”
Section: Methodsmentioning
confidence: 99%
“…CXCL1 controls neutrophil recruitment (one arm) and neutrophil function (other arm). In one arm, CXCL1 activates NF-κB, MAPK (3) and upregulation of cell adhesion molecules (ICAM-1) along with the production of cytokines/chemokines (4) in order to induce neutrophil recruitment to the tissues from the bloodstream (5). In the second arm, CXCL1 regulates the production of IL-17 (IL-17A) (6) resulting in the production of CXCL2/MIP-2 and IL-6 (7) in order to induce neutrophil recruitment (8).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of STAT2 and not STAT3 is indicative of activation of specific intracellular pathways. STAT2 is a critical component of type I IFN signalling, but is not thought to participate in TLR associated signalling (Alazawi et al, 2013). STAT2 signalling is induced predominantly by type I and type III IFN receptors suggesting that activation of STAT2 in our studies is due to autocrine IFN signalling.…”
Section: Discussionmentioning
confidence: 61%